Eksperimen Sains Sederhana: Metode untuk Meningkatkan Minat Belajar - Adam Adam; Nur Apni; Maria Rosalia; Yuliana Aisyah Achmad (LP3M Universitas Muhammadiyah Kendari, 2022)
The purpose of this study was to determine the teacher's efforts in increasing children's interest in learning. Seeing the teaching and learning process is the core business of education. In this process, students often have no interest in improving the quality of their learning. In the end the results or student achievement becomes low, and can increase barriers and difficulties in learning. The problem that often arises is the lack of interest in children's learning when studying in class. The research method used in this research is a simple science experiment. To answer the problems above, the researcher conducted a study using classroom action research. This research was conducted at RA AL-HIKMAH. Subjects in the study amounted to 11 children. Data collection techniques were carried out through observation, interviews and documentation. Based on the results of the pre-study, Experiment I and Experiment II there was an increase in children's interest in learning. It can be seen in the increase in children's interest in learning with very good criteria from none to 4 children (36.4%) and good criteria also an increase in learning interest from 3 children (27.3%) to 5 children (45.4%) in the Experiment II. So that this research is declared to have met the requirements for success above 80% on the criteria of good and very good.